2017
DOI: 10.1002/mus.25510
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography assessment of the median nerve in leprosy patients

Abstract: MN/FDSM strain ratios were significantly lower in LP with reactions. UE may be useful for nerve elasticity evaluation in leprosy. Muscle Nerve 56: 393-398, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Relative increase in median nerve stiffness was also found in patients with systemic sclerosis, leprosy, and acromegaly without reported clinical CTS, although only one of three studies reported results of electrodiagnostic studies. [41][42][43] Although the significance of these studies is difficult to ascertain without baseline electrodiagnostic studies, given that the conditions may all be associated with peripheral nerve injury, the results suggest that "cutoff" values for the diagnosis of CTS will differ among patients with other medical conditions affecting the peripheral nervous system, and should not necessarily be stand-alone values to be applied blindly.…”
Section: Cts and The Median Nervementioning
confidence: 98%
“…Relative increase in median nerve stiffness was also found in patients with systemic sclerosis, leprosy, and acromegaly without reported clinical CTS, although only one of three studies reported results of electrodiagnostic studies. [41][42][43] Although the significance of these studies is difficult to ascertain without baseline electrodiagnostic studies, given that the conditions may all be associated with peripheral nerve injury, the results suggest that "cutoff" values for the diagnosis of CTS will differ among patients with other medical conditions affecting the peripheral nervous system, and should not necessarily be stand-alone values to be applied blindly.…”
Section: Cts and The Median Nervementioning
confidence: 98%
“…and compensates for the limitations of conventional ultrasound in the detection of tumors and other diseases. 63,64 Few studies have assessed changes in the elasticity of the peripheral nerves in diabetic patients with or without diabetic neuropathy, although some studies have demonstrated that such assessment has potential for characterizing diabetic neuropathy. The value of SWE in detecting DPN of the tibial nerve in diabetic DPN patients has been shown to be higher than that of HRU.…”
Section: Improving the Diagnostic Value In Dpn By Shear Wave Sonoelasmentioning
confidence: 99%
“…Studies vary between describing each of the sonographic features/changes found in leprotic neuropathies, like color Doppler, 32,33 thickening at entrapment sites, 32,34–36 changes in nerve echotexture, 32,34,37,38 diffuse or localized changes of increased CSA of the nerve, 34,35 and/or increased epineural thickness 39 . Even newer techniques such as contrast‐enhanced ultrasound and elastography have been described in leprosy 40,41 . Studies focusing on demonstrating the importance of increased vascularization (intraneural or perineural) interpreted this as a sign of inflammation, and furthermore, as a sign of inflammatory reaction (acute or subacute) in the nerve 32,34,35,42,43 (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%